Staphylococcus lugdunensis endocarditis with destruction of the ventricular septum and multiple native valves. (2017) - Ishiekwene, Celestine; Ghitan, Monica; Kuhn-Basti, Margaret; Chapnick, Edward; Lin, Yu Shia
Abstract: Staphylococcus lugdunensis (S. lugdunensis) is a coagulase negative staphylococcus (CoNS) that can cause destructive infective endocarditis. S. lugdunensis, unlike other CoNS, should be considered to be a pathogen. We report the first case of S. lugdunensis endocarditis causing ventricular septal defect and destruction of the aortic and mitral valves. A 53-year-old male with morbid obesity and COPD presented with intermittent fever and progressive shortness of breath for 2 weeks. Chest examination showed bilateral basal crepitations, and a grade 2 systolic murmur along the right sternal border. The leukocyte count was 26, 000 cells/μl with 89% neutrophils. He was treated with intravenous vancomycin and ceftriaxone. Blood cultures grew Staphylococcus lugdunensis . Transthoracic echocardiogram, which was limited by body habitus, showed no definite valvular vegetations. Repeat transthoracic echocardiogram performed one week later revealed a large aortic valve vegetation Vancomycin was switched to daptomycin on day 4 because of difficulty achieving therapeutic levels of vancomycin and the development of renal insufficiency. Open heart surgery on day 10 revealed aortic valve and mitral valve vegetations with destruction, left ventricular outflow tract (LVOT) septal abscess and ventricular septal defect (VSD). Bio-prosthetic aortic and mitral valve replacement, LVOT and VSD repair were done. Intraoperative cultures grew Staphylococcus lugdunensis . The patient was discharged home with daptomycin to complete 6 weeks of treatment. S. lugdunensis can cause rapidly progressive endocarditis with valve and septal destruction. Early diagnosis and therapy are essential, with consideration of valve replacement.